Molecular cloning of kman coding for mannanase from Klebsiella oxytoca KUB-CW2-3 and its hybrid mannanase characters - Pongsapipatana, Nawapan; Damrongteerapap, Piyanat; Chantorn, Sudathip; Sintuprapa, Wilawan; Keawsompong, Suttipun; Nitisinprasert, Sunee (Enzyme and microbial technology, 2016)
•Mannanase gene from K. oxytoca KUB-CW2-3 was cloned into pFlag-CTS by E.coli system.•The clone KMAN-3 showed higher mannanase activity than the wild type for 400 times.•Wide substrate specificity and high productivity indicated its novel mannanase source.•Its hydrolysates enhancing beneficial bacterial growth showed prebiotic characters. Gene encoding for β-mannanase (E.C 3.2.1.78) from Klebsiella oxytoca KUB-CW2-3 was cloned and expressed by an E. coli system resulting in 400 times higher mannanase activities than the wild type. A 3314bp DNA fragment obtained revealed an open reading frame of 1164bp, namely kman-2, which encoded for 387 amino acids with an estimated molecular weight of 43.2kDa. It belonged to the glycosyl hydrolase family 26 (GH26) exhibited low similarity of 50–71% to β-mannanase produced by other microbial sources. Interestingly, the enzyme had a broad range of substrate specificity of homopolymer of ivory nut mannan (6%), carboxymethyl cellulose (30.6%) and avicel (5%), and heteropolymer of konjac glucomannan (100%), locust bean gum (92.6%) and copra meal (non-defatted 5.3% and defatted 7%) which would be necessary for in vivo feed digestion. The optimum temperature and pH were 30–50°C and 4–6, respectively. The enzyme was still highly active over a low temperature range of 10–40°C and over a wide pH range of 4–10. The hydrolysates of konjac glucomannan (H-KGM), locust bean gum (H-LBG) and defatted copra meal (H-DCM) composed of compounds which were different in their molecular weight range from mannobiose to mannohexaose and unknown oligosaccharides indicating the endo action of mannanase. Both H-DCM and H-LBG enhanced the growth of lactic acid bacteria and some pathogens except Escherichia coli E010 with a specific growth rate of 0.36–0.83h−1. H-LBG was more specific to 3 species of Weissella confusa JCM 1093, Lactobacillus reuteri KUB-AC5, Lb salivarius KL-D4 and E. coli E010 while both H-KGM and H-DCM were to Lb. reuteri KUB-AC5 and Lb. johnsonii KUNN19-2. Based on the nucleotide sequence of kman-2 containing two open reading frames of 1 and 2at 5′ end of the +1 and +43, respectively, removal of the first open reading frame provided the recombinant clone E. coli KMAN-3 resulting in the mature protein of mannanase composing of 345 amino acid residues confirmed by 3D structure analysis and amino acid sequence at N-terminal namely KMAN (GenBank accession number KM100456). It exhibited 10 times higher extracellular and periplasmic total activities of 17,600 and 14,800 units than E. coli KMAN-2. With its low similarity to mannanases previously proposed, wide range of homo- and hetero-polysaccharide specificity, negative effect to E. coli and most importance of high production, it would be proposed as a novel mannanase source for application in the future.